2022
DOI: 10.1111/ffe.13870
|View full text |Cite
|
Sign up to set email alerts
|

Multiaxial low cycle fatigue behavior and life prediction of CP‐Ti under non‐proportional stress‐controlled mode

Abstract: Multiaxial low cycle fatigue tests under non‐proportional stress (NPSS) controlled mode were performed on commercial pure titanium (CP‐Ti). Strain responses of axial and torsional channels under highly applied stress amplitudes show an initial hardening phenomenon. Non‐proportional hardening coefficient of CP‐Ti is independent of the controlled mode. The critical plane of CP‐Ti under NPSS controlled mode is aligned with the maximum principal stress plane proved by optical microscopy observation. Optimized FSM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In this regard, Ronchei et al 24 also presented a new criterion for engineering components, which is applicable to different metals with two different non‐proportional sensitivities. Ma et al 25 used commercial pure titanium as the research object to perform fatigue experiment under stress‐controlled conditions, and the results suggested that the additional strengthening of the material and the control model are independent.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Ronchei et al 24 also presented a new criterion for engineering components, which is applicable to different metals with two different non‐proportional sensitivities. Ma et al 25 used commercial pure titanium as the research object to perform fatigue experiment under stress‐controlled conditions, and the results suggested that the additional strengthening of the material and the control model are independent.…”
Section: Introductionmentioning
confidence: 99%